Genetic mapping of quantitative trait loci for the stigma exsertion rate in rice (Oryza sativa L.) - Md Habibur Rahman (Journal of Integrative Agriculture, 2017)
The efficiency of hybrid rice seed production can be improved by increasing the percentage of exserted stigmas. To identify quantitative trait loci (QTLs) for this trait, we conducted QTL mapping using 75 chromosome segment substitution lines (CSSLs) developed from a cross between the donor parent, Xieqingzao B (XQZB), a maintainer line which has high stigma exsertion and the recurrent parent, Zhonghui 9308 (ZH9308), a restorer line which has low stigma exsertion. A total of nine QTLs (qSSE5, qSSE10, qSSE11, qDSE10, qDSE11, qTSE5, qTSE6, qTSE10, and qTSE11) for single stigma exsertion (SSE), dual stigma exsertion (DSE) and total stigma exsertion (TSE) were assessed in two environments (Hainan and Zhejiang). Six of these QTLs (qSSE10, qSSE11, qDSE10, qDSE11, qTSE10, and qTSE11) were found in both environments, while one QTL (qTSE6) was found in only Hainan, and two QTLs (qSSE5 and qTSE5) were found in only Zhejiang. The qSSE10, qSSE11, qDSE10, qDSE11, qTSE6, qTSE10, and qTSE11 alleles, which are derived from the parent XQZB, exhibited a positive additive effect. In contrast, the qSSE5 and qTSE5 alleles, which are derived from the parent ZH9308, exhibited a negative additive effect. The SSE, DSE and TSE traits were significantly correlated with each other in an environmentally dependent manner. These results indicated that the lines showing higher values for SSE were more likely to exhibit increased values for DSE, which would ultimately increase TSE. To evaluate the advantage of exserted stigmas for cross-pollination, single, dual and total stigma exsertion should be considered separately in future attempts at genetic improvement to achieve increased production of rice hybrid seeds. This study also provides information for fine mapping, gene cloning and particularly marker-assisted selection (MAS), on the latter and with an emphasis the phenotypic effects and implications of the QTLs for practical use in hybrid rice breeding.